Testing the Concentration of the Bacillus subtilis BNt8 Formulation on the Growth of Corn Seeds (Zea mays L.) in Vitro - Fitrianti, Irma (Contributions of Central Research Institute for Agriculture, 2023)
Corn (Zea mays L.) is a food plant that is rich in carbohydrates. Bacillus subtilis bacteria are rod-shaped bacteria packaged as formulations. The B. subtilis BNt8 formulation is a bacterial culture obtained from Bone Regency, South Sulawesi, which can stimulate the growth of corn plants. The advantage of the B. subtilis BNt8 formulation is that the nutrients it contains are more quickly available and easily absorbed by plants. This research aims to determine the effect of various concentrations of B. subtilis BNt8 formulations on the growth of corn seeds. This type of research is quantitative research. The research approach used was a laboratory experiment using a one-factor Completely Randomized Design (CRD) with 8 treatments and 3 replications so that there were 24 experimental units, namely 0.5 gr/ml water (P1), 0.75 gr/ml water (P2 ), 1 gr/ml water (P3), 1.25 gr/ml water (P4), 1.5 gr/ml water (P5), 1.75 gr/ml water (P6), 2 gr/ml water ( P7) and control without formulation. The results obtained from this research were that B. subtilis BNt8 formulations with various treatment concentrations had no significant effect on root length, sprout length and plant fresh weight.